(3Odjd GdUMaj aj GdYGde GdKGdK (B/s - (3gSJQ, CdHQJs; (3Jh(B,(3hGj dGf(B;(3YHO GdQDha(B,(3ceGds ((3GdbGgQI(B;(3GdhdGjGJ GdeJMOI GdCeQjcjI (B:s (3GdOGQ GdOhdjI ddfTQ h GdJhRjY ,s, 1988)
(3JQi gd gfGc SHH jOYh dJGdja gPG GdcJGH GdehLg HGdJMOjO ddUMajjf aj Ohd GdYGde GdKGdK ? HGdJCcjO fYe abO OCH GdUMaj h aj GdYGde GdKGdK Ydi Gdbhd HCfge Jdbh JOQjHG UMajG aefge jSJNOehf aj cKjQ ef GdGMjGf cJHG cGf GdgOa efgG JOQjH GdUMajjf GdGeQjcjjf h GdGhQhHjjf (B. (3Pdc dCf eYXe cJH GdUMGaI GdUGOQI HGddZI GdGfLdjRjI JGJj ef GdhdGjGJ GdeJMOI h gj eDdaI NUjUG ddShb GdCeQjcjI h JSJNOe eUWdMGJ GeQjcjI h JfGSH JeGeG GdEWGQ GdELJeGYj GdGeQjcj h GdUMajhf aj GdOhd GdfGejI bO jJaHdhf HYV GdeKd GdhGQOI aj gPg GdcJH GdGLfHjI cfeGPL ddeMGcGI Ohhf Gf jYedh Ydi JYOjdgG dJdGFe GdXQha GdeMdjI dbQGA UMa GdYGde GdKGdK GdJj jYedhf HgGs
Keywords: (3GdYGde GdKGdKs; (3GdUMGaI GdKhQjIs; (3GdUMaj aj GdYGde GdKGdKs; (3GdeQCI s